Cytotoxic effect of dental luting cement on human gingival mesenchymal stem cell and evaluation of cytokines and growth factor release - An in vitro study - Iti Jain; Nayana Anasane; Amit Jagtap (Wolters Kluwer Medknow Publications, 2024)
Aim: In routine dental care, various dental luting cements are utilized to cement the dental prosthesis. Thus, the aim of the current study was to assess the Cytotoxic effect of three different dental luting cements on human gingival mesenchymal stem cell and evaluation of cytokines and growth factors release. Settings and Design: Cytotoxicity of glass ionomer cement (GIC), resin modified glass ionomer cement (RMGIC) and resin cement (RC) on the human gingival mesenchymal stem cells (HGMSCs) was evaluated. Amongst the cements tested, least cytotoxic cement was further tested for the release of cytokines and growth factors. Materials and Methods: MTT test was used to evaluate the cytotoxicity of the dental luting cements at 1 h, 24 h, and 48 h on HGMSCs. Cytokines such as interleukin (IL) 1α & IL 8 and growth factors such as platelet derived growth factor & transforming growth factor beta release from the least cytotoxic RC was evaluated using flow cytometry analysis. Statistical Analysis Used: The mean absorbance values by MTT assay and cell viability at various time intervals between four groups were compared using a one way analysis of variance test and Tukey's post hoc test. The least cytotoxic RC group and the control group's mean levels of cytokines and growth factors were compared using the Mann-Whitney test. Result: As exposure time increased, the dental luting cement examined in this study were cytotoxic. RC was the least cytotoxic, RMGIC was moderate and glass ionomer cement showed the highest cytotoxic effect. Concomitantly, a significant positive biological response of gingival mesenchymal stem cells with the release of ILs when exposed to the RC was observed. Conclusion: For a fixed dental prosthesis to be clinically successful over the long term, it is imperative that the biocompatibility of the luting cement be taken into account in order to maintain a healthy periodontium surrounding the restoration.